CORPORATE GOVERNANCE IN THE EFFORT OF INCREASING THE COMPANY’S VALUE - Nurul Hasanah Uswati Dewi (Journal of Economics, Business, and Accountancy Ventura, 2012)
It is important for the company to have its high value because it resembles the spirit of shareholdersincreasing wealth. The higher share prices make the higher the value of companystock. This study tries to examine the impact of the implementation of corporate governanceon company value and also explores the impact of firm value to the implementation of corporategovernance. This testing carried out on the top ten corporate governance perceptionindexes (CGPI) with other companies that are not in the top ten, but still within the same industryon company value. This study examined the different value of the company as measuredby Market to Book Value Equity (MTBVE), Market to Book Value Asset (MTBVA),Tobin's Q, the ratio of Value to book value of PPE (Property, Plant, and Equipment), the Ratioof Value to Depreciation Expense, Capital Expenditure to Book Value Asset (CAPBVA)and Capital Asset Expenditure to Market Value (CAPMVA). The result shows that only thevalue of MTBVE and the variable MTBVA among the top ten companies CGPI and does notin the top ten showed a difference. Therefore, the company value as indicated by MTBVE andMTBVA of the company receiving the top ten corporate governance index is higher thancompanies that did not receive.